Does the Market Respond to Management Aggressiveness? - Wijaya, Riesanti Edie (AKRUAL: JURNAL AKUNTANSI)
This study aims to examine market behavior towards management aggressiveness from the perspective of screening theory. Screening theory assumes that the market has limited information on companies. This study provides empirical evidence about the response of capital markets to management aggressiveness. Over-aggressive management is very dangerous for the company. For this reason, the researcher also examines whether the board of commissioners, foreign institutional ownership, and the presence of auditors are capable of improving market response to management aggressiveness. This study uses 852 companies taken from companies listed on the IDX from 2016 to 2018. This study provides evidence that the market does not respond to management aggressiveness. This means that the screening theory is able to explain that the market does not consider whether management is aggressive or not in making investment decisions. However, the existence of foreign institutional ownership as well as the existence of auditors is something that is considered by the market. The market has responded positively to their existence in suppressing management aggressiveness. Thus, Screening theory proves that the market has limited information about company management. However, they require different information from that provided by management in making strategic decisions.